1998
DOI: 10.1038/bjc.1998.510
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 2-(4-aminophenyl)benzothiazoles on growth of human ovarian carcinoma cells in vitro and in vivo

Abstract: Summary 2-(4-Aminophenyl)benzothiazole molecules substituted in the 3 position of the phenyl ring with a halogen atom or methyl moiety comprise a group of compounds that potently inhibit specific human ovarian carcinoma cell lines. G150 values fall within the nm range. Inhibition is highly selective -whereas the G150 value in IGROV1 cells consistently lies at < 10 nM, SK-OV-3 presents G150 values > 10jIM. Biphasic dose-response relationships were observed in sensitive cell lines after 48-h drug exposure. COMPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 11 publications
2
46
0
Order By: Relevance
“…Acquired resistance to CJM 126 conferred cross-resistance to 3′ substituted analogues (Table 1). In the NCI COMPARE program Pearson Correlation Coefficients above 0.7 were observed only between 2-(4-aminophenyl)benzothiazole analogues (Bradshaw et al, 1998b). Such observations indicate shared mechanisms of action.…”
Section: Discussionmentioning
confidence: 94%
“…Acquired resistance to CJM 126 conferred cross-resistance to 3′ substituted analogues (Table 1). In the NCI COMPARE program Pearson Correlation Coefficients above 0.7 were observed only between 2-(4-aminophenyl)benzothiazole analogues (Bradshaw et al, 1998b). Such observations indicate shared mechanisms of action.…”
Section: Discussionmentioning
confidence: 94%
“…Compounds 3,6,8,10,11,12,16,18 and 20 were selected by NCI for 60 human tumor cell lines' anticancer screening test at single dose assay. In vitro single-dose anticancer assay was performed in full NCI 60 cell panel representing L, NSCLC, CC, CNSC, M, OC, RC, PC, and BC.…”
Section: Resultsmentioning
confidence: 99%
“…Unexpectedly, it was found that, 2-(4-aminophenyl)benzothiazole derivatives inhibit cancer cell growth with nanomolar scale against a large panel of human cancer cell lines particularly against breast, colon and ovarian cell lines in in vitro anticancer screening program of the National Cancer Institute (NCI) with a characteristic biphasic doseresponse relationship 6,7 . Up to present, scientists Shi and Bradshaw have a series of studies on antitumor activity of some benzothiazole derivatives [8][9][10][11][12][13][14] . First, the original lead compound 2-(4-aminophenyl)benzothiazole (CJM 126, NSC34445), which was originally prepared as a synthetic intermediate in a program of screening for tyrosine-kinase inhibitors, was found to possess selective in vitro activity against MCF-7 breast carcinoma cell line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Substituted 2-(4-aminophenyl)benzothiazoles were developed and examined, in vitro, for their antiproliferative activity in ovarian, breast, renal and colon carcinoma human cell lines, [5][6][7][8] imidazo benzothiazoles, 9,10 as well as, polymerized benzothiazoles 11 and other substituted benzothiazoles 12 showed remarkable antitumor activity against malignant cell lines. The aryl amines, 2-(4-amino-3-methylphenyl)benzothiazole, 13 were deduced from comparison with compounds 5a-k.…”
Section: Introductionmentioning
confidence: 99%